Monad of the hyperspaces of inclusion and its algebras - Radul, T. N. (Ukrains’kyi Matematychnyi Zhurnal, 1990)
A monad (in the Eilenberg-Moore sense) on the category of compact spaces is constructed; it is defined by the inclusion hyperspace functor. The category of algebras of this monad is described and a characterization of the free algebras is given.